Original paperAge-dependent neuroprotection of retinal ganglion cells by tempol-C8 acyl ester in a rat NMDA toxicity model - Fiedorowicz, Michal; Rejdak, Robert; Schuettauf, Frank; Wozniak, Michal; Grieb, Pawel; Thaler, Sebastian (Folia Neuropathologica, 2014)
Background : The efficacy of tempol and its acyl derivative tempol-C8 as retinoprotective agents was compared in a rat model of NMDA-induced retinal ganglion cell (RGC) damage. Material and methods : Tempol or tempol-C8 in different doses was administered intraperitoneally to 6 weeks old (pre-adolescent) and 9-10 weeks old (young adult) rats before and after an intravitreous NMDA injection. Retinal ganglion cell were retrogradely labeled with the fluorescent tracer hydroxystilbamidine and RGC counting was performed on retinal flatmounts. Results: Intravitreal NMDA reduced RGC counts by about 90%, independently of age (p < 0.001). In pre-adolescent animals tempol-C8, but not tempol unmodified, showed a significant, dose-dependent RGC rescue effect, with peak activity at 5.8 µmol/kg (p < 0.001). In young adult animals, however, no neuroprotective effect was found for either tempol or tempol-C8. Conclusions : In contrast to tempol itself, tempol-C8 acyl ester was neuroprotective in pre-adolescent rats in the NMDA- induced RGC damage model. Therefore, neuroprotection by tempol acyl esters seems to be superior to that of tempol under certain conditions.